Drone analysis of medieval fortifications: the district of Loja in the Nasrid kindgom of Granada (Spain) - Luis José García-Pulido; Jonathan Ruiz-Jaramillo; Sara Peñalver-Martín (Disegnare con)
The last Islamic kingdom in the Iberian Peninsula was ruled by the Nasrid dynasty during the thirteenth to fifteenth centuries around Granada. It was divided into about twenty administrative districts, and Loja, located in the northern center area, was one of the most important and strategic ones. It had a high density of fortifications of different nature, some of which date back to very ancient times. This contribution is the result of the intense digital documentation that has been carried out on the graphic representation of these assets. They have been completed with the use of Unmanned Aerial Vehicles (UAV) to obtain the necessary graphic information to represent these architectures by means of precise planimetrical surveys, documenting and diagnosing their current state. DOI: https://doi.org/10.20365/disegnarecon.29.2022.9